The six rules of maybe - Caletti, Deb. (New York : Simon Pulse, 2010)
Scarlet, an introverted high school junior surrounded by outcasts who find her a good listener, learns to break old patterns and reach for hope when her pregnant sister moves home with her new husband, with whom Scarlet feels an instant connection.
820
Keywords: Interpersonal relations -- Juvenile fiction; Sisters -- Juvenile fiction; Pregnancy -- Juvenile fiction; Mothers and daughters -- Juvenile fiction; Family life -- Oregon -- Juvenile fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction; Oregon -- Juvenile fiction